Development of the Single Area Payments Scheme in the Visegrad Countries - Osztrogonácz, Ivó (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
One of the most important date for the Visegrad Countries2 was year 2004, because of the accession to the EU. The four countries have to apply the Common Agricultural Policy (CAP) which provides facilities for the farmers in form of direct payment, market measures, agricultural and rural development programs. The analyses of the direct payments development in the Visegrad Countries are necessary for the further CAP reform